Occurrence features of Rip current at Ha My (Dien Ban district) and Tam Thanh (Tam Ky city) beaches, Quang Nam province - Mau, Le Dinh; Tuan, Nguyen Van; Cong, Nguyen Chi; Binh, Tran Van; Trung, Pham Ba; Hoan, Pham Sy; Hoang, Ngo Quang Bao; Tuyen, Phan Thi Ha (Vietnam Journal of Marine Science and Technology, 2019)
Rip current is a relatively strong, narrow current flowing outward from the beach through the surf zone and presenting a hazard to swimmers. This paper presents some occurrence features of Rip current at main swimming beaches in Quang Nam province, Central Vietnam. Study results show that most of swimming beaches along Quang Nam province coast are directly opposed to open sea and strongly affected by swell. Therefore, Rip current system can occur at any time in the year with large dimension and intensity. During Northeast monsoon (November to March) beach morphology is considerably changed by strong wave action, thus the strongest rip current is formed. However, in this period careful swimmers can easily identify where that rip current occurs along the beach. During the transition period from Northeast monsoon to Southwest monsoon (April to May) wave energy is reduced, thus Rip current intensity is also decreased. During Southwest monsoon (June to August) wave energy is not strong and beach is accreted, therefore some Rip currents remain at reasonable morphology places along the beach. During the transition period from Southwest monsoon to Northeast monsoon (September to October) Rip current can occur at deep places along the beach with characteristics of narrow dimension, thus causing more danger to swimmer. Especially, dangerous rip current is caused by swell which comes from active region of tropical cyclone in open sea. In this period wave field in the nearshore region is not rough, thus most of swimmers are not cautious when swimming at dangerous rip current places.